Antiproliferative effects of hazelnut cell culture extract on the different cancer cell lines: Antiproliferative effects of hazelnut cell culture extract - Ari, Sule; Cetin, Idil; Dogan, Ahmet; Topcul, Mehmet Rifki (Cellular and Molecular Biology, 2024)
The increasing incidence of cancer has necessitated the discovery of novel anticancer compound sources. The presence of taxanes in hazelnut cell cultures has promoted new promising pharmacotherapeutic applications. The antiproliferative properties of hazelnut (Corylus avellana cv. ‘Kalınkara’) cell culture extracts against different human cancer cell lines (HeLa, MCF-7, MDA-MB-231, A549) with Beas-2B as control were evaluated. The cytotoxicity of C. avellana culture extract (5 µM, 10 µM, and 20 µM) on all cell lines was evaluated with xCELLigence Real Time Cell Analysis System. Mitotic activity (450-655 nm), BrdU activity (450-550 nm) and caspase 3,7 activity (490-520 nm) were analyzed with a spectrophotometer through 24, 48, and 72 hours. Based on the values obtained from the xCELLigence Cell Analysis System, a 10 µM concentration of the culture extract was assigned as the IC50 dose. Culture extracts at 10 µM enhanced the reduction in the proliferation of all cancer cells assayed. The highest decrease in mitotic (59.32%) and BrdU (53.77%) activity was observed in A549 lung cancer cells. However, caspase 3,7 activity (35.08%) was the highest in aggressive MDA-MB-231 breast cancer cells. The culture extracts decreased the viability of A549 cells to a greater extent than that of MCF-7 and MDA-MB-231 breast, and HeLa cervical cancer cells. C. avellana cv. ‘Kalınkara’ cell culture extracts have potential use in the treatment of lung and, to a lesser extent, breast and cervical cancers.